Sifat Fisis Dan Mekanis Pada Komposit Polyester Serat Batang Pisang Yang Disusun Asimetri [ 45o / -30o / 45o / -30o ] - Irsyad, Mirwan; , Ir. Ngafwan, MT; , Agus Yulianto, ST. MT (2015)
The aim of this study was to describe the tensile strength, bending strength and fracture macro photo on banana stem fiber polyester composites prepared asymmetry [45o / -30o / 45o / -30o] to change teperature test on tensile test and bending test. The initial process of making composites are making fibers from banana trees followed by immersion for 2 hours using a chemical solution of kalium pemangante (KMnO4) by 2% per 1 liter of distilled water. Drying under the sun to dry continued with the process of oven for 1 hour at a constant temperature of 35oC until the moisture content of 10%. Then the fibers are arranged at an angle of orientation of asymmetry [45o / -30o / 45o / -30o] using paper prints, be continued with the provision of the resin was conducted using hand lay-up on the glass mold that has been measured in accordance with the standards. The resin used is a thermosetting resin types, namely polyester BQTN series 157 with increasing catalyst (hardener) as much as 1% of the volume of resin. Tensile test using the ASTM D 3039 standard while bending tests using standard ASTM D 7264 with a variation of room temperature, test temperature of 35oC, 45oC and 55oC. Results of tensile test can be concluded that the tensile strength at room temperature is 11.530 N / mm2, the temperature variation of the tensile test, the greater the given temperature tensile strength will increasingly come down from 15.520 N / mm2 at a temperature test 35oC be 9.502 N / mm2 at temperatures 55oC test. While the test results of bending can be concluded that the bending strength at room temperature is 0.151 N / mm2, the temperature variation of bending test, the higher the temperature of a given strength of bending will experience kenakian of 0,339 N / mm2 at a temperature test 35oC be 6.215 N / mm2 at temperatures test 55oC.